ANALISIS EFEK MEDIASI KEPUASAN SISWA ATAS PENGARUH KUALITAS LAYANAN, CITRA SEKOLAH, PERSEPSI TENTANG HARGA, TERHADAP TINGKAT KEPERCAYAAN SISWA - Sitorus, Tigor; Suwarno, Suwarno (Jurnal Manajemen, 2015)
This study aims to determine the influence of Service Quality, School Image and Perception Price for Student Satisfaction and Student Trust. This research was conducted at the Vocational High School (SMK) Private in West Jakarta, which spread in 8 (eight) districts with a total sample of 200 students. Structural Equation Modelin (SEM) by AMOS program version 22 used to prove the affecting of among variables, with conclusions as follows: first; Service Quality has positive and significant  effect on Student Satisfaction,  second; School Image has positive and significant  effect on Student Satisfaction,  Third; Perception Price has positive  effect but not significant on Student Satisfaction,   Fourth; Service Quality has positive  effect but not significant on Student Trust,  Fifth; School Image has positive effect but not significant on Student Trust, Sixth; Perception Price has positive effect and significant Student Trust, Seventh; Student Satisfaction has positive effect and significant  on Student Trust, and the eighth, mediating effect of student satisfaction more strength and significant than direct effect of service quality and school image on student trust.